Answer:
The point (0, 1) represents the y-intercept.
Hence, the y-intercept (0, 1) is on the same line.
Step-by-step explanation:
We know that the slope-intercept form of the line equation
y = mx+b
where
Given
Using the point-slope form
![y-y_1=m\left(x-x_1\right)](https://tex.z-dn.net/?f=y-y_1%3Dm%5Cleft%28x-x_1%5Cright%29)
where
- m is the slope of the line
In our case:
substituting the values m = 2/3 and the point (-6, -3) in the point-slope form
![y-y_1=m\left(x-x_1\right)](https://tex.z-dn.net/?f=y-y_1%3Dm%5Cleft%28x-x_1%5Cright%29)
![y-\left(-3\right)=\frac{2}{3}\left(x-\left(-6\right)\right)](https://tex.z-dn.net/?f=y-%5Cleft%28-3%5Cright%29%3D%5Cfrac%7B2%7D%7B3%7D%5Cleft%28x-%5Cleft%28-6%5Cright%29%5Cright%29)
![y+3=\frac{2}{3}\left(x+6\right)](https://tex.z-dn.net/?f=y%2B3%3D%5Cfrac%7B2%7D%7B3%7D%5Cleft%28x%2B6%5Cright%29)
Subtract 3 from both sides
![y+3-3=\frac{2}{3}\left(x+6\right)-3](https://tex.z-dn.net/?f=y%2B3-3%3D%5Cfrac%7B2%7D%7B3%7D%5Cleft%28x%2B6%5Cright%29-3)
![y=\frac{2}{3}x+4-3](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B2%7D%7B3%7Dx%2B4-3)
![y=\frac{2}{3}x+1](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B2%7D%7B3%7Dx%2B1)
comparing with the slope-intercept form y=mx+b
Here the slope = m = 2/3
Y-intercept b = 1
We know that the value of y-intercept can be determined by setting x = 0, and determining the corresponding value of y.
Given the line
![y=\frac{2}{3}x+1](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B2%7D%7B3%7Dx%2B1)
at x = 0, y = 1
Thus, the point (0, 1) represents the y-intercept.
Hence, the y-intercept (0, 1) is on the same line.
A , because you have to divide it so you can get the correct answer
sum is an answer to an addition problem, so we have to add 43 and z. z+43=72.98
Subtract 43 on both sides.
z=29.98
---
hope it helps
Answer:
(180-x)⁰ or it might also be X⁰
Here, 3m is a scalar that we use to multiply each element of the matrix.
We have
![3m \left[\begin{array}{cc}-5m&2m\\6m&6n\end{array}\right]](https://tex.z-dn.net/?f=%20%203m%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D-5m%262m%5C%5C6m%266n%5Cend%7Barray%7D%5Cright%5D%20)
.
We get
![\left[\begin{array}{cc}(3m)(-5m)&(3m)(2m)\\(3m)(6m)&(3m)(6n)\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D%283m%29%28-5m%29%26%283m%29%282m%29%5C%5C%283m%29%286m%29%26%283m%29%286n%29%5Cend%7Barray%7D%5Cright%5D%20)
which simplifies to